Implementasi Data Mining terhadap Pola Penjualan Bahan Material Bangunan di TB. Murah Rejeki Menggunakan Algoritma Apriori - Muhammad Ali Ridla; Achmad Baijuri; Ubaidillah Ahmad (Institut Informatika dan Bisnis Darmajaya, 2023)
The Murah Rejeki Building Store makes sales transactions every day, but these transactions are only used for reporting and data bookkeeping purposes. The Murah Rejeki Building Store has not conducted an analysis of the relationship between building material products purchased by consumers in the future. This study aims to process sales transaction data from consumer purchases using the Apriori Algorithm, which is one of the data mining processing methods. In this study, the authors use the Apriori Algorithm to find association rules by determining the Minimum Support and Minimum Confidence values. The results showed that with a Minimum Support value of 5% and a Minimum Confidence of 60%, 14 patterns of consumer purchase transactions were found. This information becomes very valuable in making decisions on preparing supplies of building materials and determining the layout of goods in TB. Cheap Fortune. The association rules formed can be used to plan sales strategies and layout of building materials at TB. Murah Rejeki.